27-Hydroxycholesterol in cancer development and drug resistance - Yaxin Hou; Zhiguang Fu; Chenhui Wang; Paulina Kucharzewska; Yuan Guo; Sihe Zhang (Journal of Enzyme Inhibition and Medicinal Chemistry)
27-Hydroxycholesterol (27HC), a cholesterol metabolite, functions both as a selective oestrogen receptor (ER) modulator and a ligand for liver X receptors (LXRs). The discovery of 27HC involvement in carcinogenesis has unveiled new research avenues, yet its precise role remains controversial and context-dependent. In this review, we provide an overview of the biosynthesis and metabolism of 27HC and explore its cancer-associated signalling, with a particular focus on ER- and LXR-mediated pathways. Given the tissue-specific dual role of 27HC, we discuss its differential impact across various cancer types. Furthermore, we sort out 27HC-contributed drug resistance mechanisms from the perspectives of drug efflux, cellular proliferation, apoptosis, epithelial–mesenchymal transition (EMT), antioxidant defence, epigenetic modification, and metabolic reprogramming. Finally, we highlight the chemical inhibitors to mitigate 27HC-driven cancer progression and drug resistance. This review offers an updated role of 27HC in cancer biology, setting the stage for future research and the development of targeted therapeutics.